Pharmacognostic studies of Morinda brevipes S. Y. Hu - Li, Rong; Lin, Xiaojing; Tang, Genqiu; Li, Junni; Wang, Dong; Ji, Shengguo (Bangladesh Journal of Botany, 2019)
DNA barcoding of ITS and psbA-trnH regions, histochemistry as well as thin layer chromatography (TLC) of Morinda brevipes S.Y. Hu were analyzed. Transverse section of root revealed the presence of cortex, xylem, cork cell, stone cells, and calcium oxalate sandy crystal. The lower epidermis cells showed many stoma in paracytic or inequality type. Spiral vessel and tiny calcium oxalate needle crystal usually appeared in the powder. TLC showed the presence of emodin in M. brevipes. Phytochemical studies revealed the existence of carbohydrates, saponins, tannins, flavones, anthraquinones, alkaloids and volatile oils. The ITS and psbAtrnH sequences were found for the first time which were submitted to NCBI to obtain the GenBank registration number. This study might play an important role in the identification, and utilization of M. brevipes for various purposes.